BIM Collaborative Design: A Critical Perspectives of Technology-Supported Multidisciplinary Practice - Babangida Idi, Danfulani,; Khaidzir , Khairul Anwar Mohamed,; Khalil, Ibrahim Sani (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Building Information Modelling (BIM) collaborative design provides a platform where all stakeholders work on one single building information model embedded with multiple digital data points for the production and construction information of the building. The platform uses hyper-computer-mediated software for functions like fabrication, assembly, animation, analysis and simulation that are generally referred to as authoring and analysis for integrated project delivery (IPD). No doubt, issues of BIM collaborative design are well established in the literature of technology-supported multidisciplinary practices such as system applications and technologies; information and data management; multidimensional ecosystems and media interactions; and scientific strategies of practice. However, grounded conceptual and conventional design and collaboration requirements are not clearly and adequately represented. Therefore, this study reviewed core design collaboration research articles using content analysis to establish the theoretical framework BIM collaborative design and subsequently established its strength and challenges. 156 out of the 176 published materials on design collaboration from 1950 to date from ScienceDirect under the licences of Bayero University, Kano and Universiti Teknologi Malaysia were selected and reviewed. In addition to the already established BIM collaborative design parameters, the content analysis revealed that; group cognition (cognitive actions and reasoning), knowledge exchange, lateral and vertical transformations were also found relevant in the theoretical framework of BIM collaborative design. The logical argumentation showed that studies on the tacit knowledge problem-solving space such as experience, skills, know-how, group cognition, knowledge transformation; assets and ’ba’ are missing in the literature of the BIM framework of collaborative design. Thus, this study concludes that, even though BIM collaborative design has been globally accepted, there is a need to extend its research and support in tacit knowledge problem-solving spaces.